Mengukur kesesuaian tugas dan teknologi penggunaan ERP di PT Angkasa Pura I Kantor Cabang Bali - Gusi Putu Lestara Permana; Ni Made Ayu Dwi Kusumardani (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2025)
Purpose - This study aims to measure the alignment between tasks and technology in the implementation of Enterprise Resource Planning (ERP) systems. Task alignment is measured using the Task Technology Fit (TTF) model. Methods - This study adopts a quantitative approach focusing on employees who are users of Enterprise Resource Planning systems. A saturated sampling technique is employed, where the entire population is considered as the sample. The data collected includes primary data obtained through questionnaires, which are evaluated using a Likert scale. Data analysis is performed using the Partial Least Squares (PLS) method. Findings - Employee performance tends to improve when technology provides features and support that align with task requirements. The level of technology utilization contributes to enhanced performance, where increased use of technology is followed by improved employee performance. Implications - This study demonstrates that the Task Technology Fit (TTF) model is relevant in measuring the alignment between tasks and technology in ERP system implementation. Originality - This study develops the Task Technology Fit model by integrating constructs from the Technology Acceptance Model, thereby revealing the relationship between task alignment, technology, and psychological factors that influence user acceptance of the technological system.